Use of edible film in the postharvest conservation of ’Magali’ sweet pepper - Moreira, Elaine Gleice Silva; Sanches, Alex Guimarães; Silva, Maryelle Barros da; Macedo, Jaqueline; Cordeiro, Carlos Alberto Martins; Costa, Shirley Silva Cosme (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The sweet pepper, like other vegetables, is a highly perishable product, because it has a very short post-harvest life. This feature, coupled with improper handling during harvesting, leads to great losses. In view of this, to evaluate the sensory quality, the physico chemical characteristics and post-harvest life of pepper cv. Magali, we used coating with film of cassava starch or corn starch. The treatments were without coating and coating with 2% or 4% of cassava starch or corn starch, at room temperature or refrigeration. Fruits were evaluated at 0, 3, 6, 9 and 12 days of storage as the loss of weight, soluble solids, titratable acidity, pH, determined maturation index TSS/TTA, fruit firmness, skin color, external physical damage, and general appearance. The experiment was factorial 5 x 5 (treatment x time). The loss of weight increased during storage, and less pronounced at a dose of 4% of cassava starch and treatment under refrigeration. The results indicate that the use of biofilms in the concentrations of 2% and 4% for cassava starch and 2% for corn starch were those that provided better results in terms of physical and chemical maintenance and sensory acceptance of sweet peppers during the storage period.